Inter-partner fit and joint venture performance: A case study on Padiberas Nasional Berhad - Tey, L.S.; Idris, A. (2009)
Although joint venture, as a corporate strategy, has been gaining popularity over the past few decades, its growth is often fraught with instability and poor performance. This paper aims to share the story of a Malaysian public listed company – Padiberas Nasional Berhad (BERNAS) – which has achieved success through joint ventures. The case highlights the significance of inter-partner fit and relations as determinants of joint venture performance. It also underlines the importance of both micro and macro factors in the determination of fit between partners.